Analyses of the Bacterial Contamination on Belgian Broiler Carcasses at Retail Level - Yu, Zhongjia; Joossens, Marie; Houf, Kurt (Frontiers in Microbiology, 2020)
Broilers are not equally exposed to bacterial contamination during rearing and processing, resulting in areas with different bacterial communities on carcasses at retail. The determination of these communities is also affected by the examination methods applied. The present study aimed to assess the bacterial communities on neck, breast and back skin on broiler carcasses at retail through classical International Organization of Standardization based isolation methods combined with identification by matrix-assisted laser desorption ionization time-of-flight mass spectrum (MALDI-TOF MS), and 16S amplicon sequencing. Twelve commercially and eight organically reared broilers slaughtered in four slaughterhouses were examined. Significantly higher anaerobic bacterial counts were observed on the neck skin than on the breast and back skin. By the combination of cultivation and amplicon sequencing, remarkable shifts in bacterial communities were determined on the breast and back skin, but not on the neck skin. Although the aerobic bacteria contamination levels were not different between the areas, different bacterial communities were observed. The impact of the slaughterhouse to the overall microbial composition was rather small. Organically reared broilers had unique bacterial communities. In conclusion, compared to the breast skin, the neck and back skin had a larger potential for bacterial spoilage, in particular when anaerobic storage conditions are applied. The distribution of bacteria on the different areas could be related to the contamination during slaughter, as well as the bird-rearing methods.